Eccentric Europe and propaganda of faith. Considerations about Sacra Congregatio de propaganda fide and its influence on the European identity of Lithuania in XVII–XVIII centuries - Mažeikis, Gintautas (Religija ir kultūra, 2007)
The main thesis about common European identity is based on the maintaining of R. Brague that identities are formed on the borders. The main power for forming self consciousness of local people as Europeans was propaganda. Propaganda is considered as systemic, rational, long-term persuasions of thinking and self evaluation of people. Propaganda seeks to construct the discourse or propaganda subject and legitimate its suggestion and behavior. The Vatican institution of propaganda was formed by popes Gregory XIII and Gregory XV. Finally Congregatio de propaganda fide was established in 1622. The firsts principles of propaganda idea were directly related to the Renaissance Studia humanitatis. P. Neri and his Congregatio oratorium continued Florence’s Christian humanism and ecstatic rhetoric of G. Sovanarola. Neri also continued some ideas of L. Valla about rhetoric manifestation of the truth. Gregory XIII supported movement and ideas of Neri. From the other side he was a patron of Society of Jesus and he established first propaganda commission for the providing of Catholic faith on the borders of European world. Gregory XIII initiated propaganda through spreading of Jesuit’s and other Christian order’s missions, colleges, universities. The propaganda and Jesuits influence on Grand Duck of Lithuania is compared with Jesuits activities in the North America. Lithuanians were very pagans in the rural spheres in this time. The protestant movement was influenced in the cities. The Vatican Episcope’s power was not popular between Lithuanian noblemen and the influence of Protestant Livonia was significance. From the civilization point of view Russian or Eurasian pressing was felt all time and many of Grand Duke of Lithuania lands were Slavs. The article seeks to show how did Jesuits form the network of education, how they competed with other Catholic orders, how they make new discipline and communities of local people. Jesuits became very important power for forming European subject on the borders of Europe in the XVII and XVIII centuries. They created new religious, scientific, political, national discourses and educational networks necessary for interpellation of subject of European civilization. Thought Russian Imperia tried to build new identities and world feeling, new educational system and propaganda after occupation of Lithuania in 1795 the European identity of Lithuanians survived on the archeological level, history of education and myths.